Effect of bleaching agents on mechanical properties of bulk fill resin and conventional composites (Research, Society and Development, 2020)
This study evaluated the effect of tooth whitening on resin composites (RC) on roughness, microhardness and flexural strength. There were three RC: one Bulk Fill type resin (Filtek Bulk Fill) and two conventional, Filtek Z350 (Z350) and Z250 (Z250). Twenty-four bar-shaped specimens were made for each RC. First, the initial roughness and microhardness were evaluated; thus, the RC were subdivided into 3 other groups, according to treatments: control group (C), this did not receive bleaching treatment; home bleaching with 10% carbamide peroxide (10%CP) (Opalescence PF),  8h/14 days; home-office bleaching with 40% hydrogen peroxide (40%HP) (Opalescence Boost PF) 3 ´ 15 minutes for 3 days at 48 hour intervals. After treatments, roughness and microhardness were again evaluated and then the samples submitted to the three-point flexural test. Data were tabulated, normality assessed, then submitted to ANOVA followed Tukey’s test (p